Dietary rationing of date pomace, tomatoes, grapes and their mixing in the initiator period and its effect on some productive traits and some fasting bacteria in the small intestine of broilers - Marwah Abd AL-Kafar Sarhan; Muhammad Joodi Shaheed (University of Thi-Qar Journal of agricultural research, 2021)
This study aims to compare the effect of diluting the feed provided to broilers with the remains of canning factories (dates, tomatoes, grapes and their mixture) on some productive traits and some jejunum bacteria. It is located in the field of poultry at the Faculty of Agriculture and Marshlands. In the experiment, 240 unsexed, 1-day-old Ros-308 chicks, average starting weight 42g, were used. Chicks were fed a standard initial diet for 1-7 days. Chicks were randomly distributed to five treatments, 48 ​​chicks for each treatment (16 chicks for each replicate). The experimental diets were used from the beginning of the second week until the end of the third week (14 days) as follows: (T1: control diet diluted with no dilution) (T2: control diet diluted with 20% date pomace) (T3): control diet diluted with 20 % tomato pomace) (T4: control diet diluted with 20 pomace) from 20% grape pomace diet (T5: control diet diluted 20% of a homogeneous and equal mixture of three types of pomace), and after the end of the third week, the serving was increased For everyone until the end of the trial period. At the end of the experiment, there were no significant differences in economic growth and growth results in traits (live weight rate, weight gain rate, feed consumption rate, feed conversion efficiency) with an arithmetic improvement in traits in all production traits. In favor of the two treatments (T5, T3), the result was a significant increase (p≤0.05) in the number of lactobacilli bacteria in the jejunal part of the small intestine with a significant decrease in the total of aerobic bacteria and Escherichia coli.